1998
DOI: 10.1111/j.1600-065x.1998.tb01185.x
|View full text |Cite
|
Sign up to set email alerts
|

The C‐type lectin superfamily in the immune system

Abstract: Protein-carbohydrate interactions serve multiple functions in the immune system. Many animal lectins (sugar-binding proteins) mediate both pathogen recognition and cell-cell interactions using structurally related Ca(2+)-dependent carbohydrate-recognition domains (C-type CRDs). Pathogen recognition by soluble collections such as serum mannose-binding protein and pulmonary surfactant proteins, and also the macrophage cell-surface mannose receptor, is effected by binding of terminal monosaccharide residues chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
670
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 967 publications
(692 citation statements)
references
References 77 publications
3
670
0
5
Order By: Relevance
“…Also, the two forms of human LF are identical in their amino acid sequence, but different in sugar moiety. The granulocytic LF is not fucosylated and this seemingly predisposes this form to transduce certain signals that do not require fucose-specific receptors such as mannose receptor exhibiting equal affinity to fucose and mannose [38]. Here, it was demonstrated that the activity of rhLF depends on the terminal N-acetylneuraminic acid.…”
Section: Discussionmentioning
confidence: 92%
“…Also, the two forms of human LF are identical in their amino acid sequence, but different in sugar moiety. The granulocytic LF is not fucosylated and this seemingly predisposes this form to transduce certain signals that do not require fucose-specific receptors such as mannose receptor exhibiting equal affinity to fucose and mannose [38]. Here, it was demonstrated that the activity of rhLF depends on the terminal N-acetylneuraminic acid.…”
Section: Discussionmentioning
confidence: 92%
“…[5][6][7] The ligands and functions of the receptors remain unknown, but the receptor type has been implicated in diverse functions, such as microbial pattern recognition, cellular adhesion and migration, antigen uptake and presentation, T cell co-stimulation, and signal transduction through immunoreceptor tyrosine-based inhibitory or activating motifs (ITIMs and ITAMs, respectively). [8][9][10][11] Interestingly, we observed earlier that APLEC regulates clinical phenotypes in RA models induced by nonimmunogenic structures that activate the innate immune system, for example, incomplete Freund's adjuvant oil and yeast b-glucan. 5 Herein, we tested the hypothesis that APLEC might also regulate infectious diseases and innate macrophage reactivity.…”
Section: Introductionmentioning
confidence: 94%
“…Lectins are a group of sugar binding proteins which are involved in both innate and adaptive immunity [53], including pathogen recognition and neutralization [54]. Furthermore, a diversity of lectins was reported in fish skin mucus [55].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%